'It's like getting an Uber for sex': social networking apps as spaces of risk and opportunity in the Philippines among men who have sex with men. Issue 3 (1st September 2020) - Hollingshead, Brooke Maria; Dowsett, Gary W.; Bourne, Adam
Abstract : The HIV epidemic in the Philippines has been expanding rapidly, with most newly diagnosed cases occurring among 'men who have sex with men' (MSM). New social contexts of HIV are evident in the evolving phenomenon of more MSM seeking partners online via social networking applications ('apps'). This study examines findings from a virtual ethnography of app use among MSM, focus group discussions with community-based healthcare workers, and key informant interviews with healthcare workers, policymakers and researchers in Metro Manila. We argue that participants viewed the expanding epidemic and apps as intimately linked, regarding the apps as 'risky spaces' for 'risky behaviour'. However, such narratives neglected the agentive capabilities of the apps and how they have transformed sexual practice, creating new ways of being as sexual subjects, while perpetuating old imaginaries among healthcare workers of 'hard-to-reach' populations. Such narratives of 'risk' have led to new interventions by healthcare workers on the apps, viewing these technologies as opportunities to reach more MSM for health promotion. However, the interventions have created new complexities by reconfiguring boundaries with target populations. By conducting community-based outreach through encouraging behaviour change in one-to-one interactions with app users, the potential impact of these interventions is limited.